2021
DOI: 10.1016/j.jds.2020.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors affecting alveolar ridge height and facial bone thickness in Chinese maxillary central incisors by cone beam CT

Abstract: Background/purpose In the immediate implantation of maxillary central incisors, the height of the alveolar bone is lost, and there is often a risk of bone fracture due to the thin buccal bone wall (BBW). The purpose of this study was to assess the effects of smoking, age, and root position in the alveolar bone on the BBW and the distance between the cemento-enamel junction (CEJ) and the facial bone crest (FBC) of Chinese maxillary central incisors. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A few sagittal root positions were Type III in maxillary incisors, suggesting that a certain degree of incisor bodily retraction is feasible. At the same time, research has found that most roots of the maxillary incisors were positioned close to the labial cortical bone [ 14 , 15 ], which is consistent with the present study that the proportion of Type II sagittal root positions was not high. At the same time, there was no significant difference in the alveolar bone thickness at each measurement site of the maxillary incisors in each group.…”
Section: Discussionmentioning
confidence: 99%
“…A few sagittal root positions were Type III in maxillary incisors, suggesting that a certain degree of incisor bodily retraction is feasible. At the same time, research has found that most roots of the maxillary incisors were positioned close to the labial cortical bone [ 14 , 15 ], which is consistent with the present study that the proportion of Type II sagittal root positions was not high. At the same time, there was no significant difference in the alveolar bone thickness at each measurement site of the maxillary incisors in each group.…”
Section: Discussionmentioning
confidence: 99%
“…Second stage bone grafting is the most common method for the treatment of alveolar cleft defect. The purpose of this approach is to reconstruct the alveolar cleft defect and restore the integrity of the maxilla ( 1 ). To help the permanent teeth around the fissure erupt normally, it is essential to provide good bone support for orthodontic treatment and nasolabial deformity rectification, as this can ensure the necessary bone mass required for further implant treatment.…”
Section: Introductionmentioning
confidence: 99%